Prediksi Kebangkrutan Menggunakan Altman Z-Score dan Zmijewski pada PT Prasidha Aneka Niaga Tbk Periode 2014-2018 - Widya Saviera Putri; Iwan Setiawan; Benny Barnas (Jurusan Akuntansi Politeknik Negeri Bandung, 2020)
The growth of the company listed on the IDX is experiencing the highest achievement as the most listed exchange of IPO in the ASEAN region. The fluctuation of the profit generated by PT. Prasidha Aneka Niaga Tbk. which tends to suffer losses in the year of research, the research aims to predict bankruptcy at PT. Prasidha Aneka Niaga Tbk. using the Altman Z-Score and Zmijewski method. The method of study that was used is a descriptive method. The data used is based on the annual financial report. The results showed that bankruptcy predictions using the Altman model of the company's Z-Score were in the grey area and had potential bankruptcy category. While bankruptcy predictions using Zmijewski the company is in a healthy category. Based on the said calculations, the company has produced different results, but judging from the ratio of each model the company is in position of vigilant bankruptcy.